Interest of pregnant women in the use of SMS (short message service) text messages for the improvement of perinatal and postnatal care - Cormick Gabriela; Kim Natalie A; Rodgers Ashlei; Gibbons Luz; Buekens Pierre M; Belizán José M; Althabe Fernando (BMC, 2012)
Abstract Background Mobile health (mHealth) is emerging as a useful tool to improve healthcare access especially in the developing world, where limited access to health services is linked to poor antenatal care, and maternal and perinatal mortality. The objective of this study is to 1) understand pregnant women's access and usage of cell phones and 2) survey the health information needs and interests in a population attending public hospitals and health centers of two cities in Argentina. This information is not available and it is the basis to develop a strategy for improving maternal care via cell phones. Methods Questionnaires were verbally administered to pregnant women who were attending an antenatal care visit in community health centers and public hospitals in Rosario, Santa Fe and Mercedes, Corrientes. Participants were 18 years of age or older and had previously given birth. The data obtained was qualitative and analyzed using SPSS version 18. Results A total of 147 pregnant women meeting inclusion criteria (Rosario: 63; Mercedes: 84) were approached and verbally consented to participate. The average age was 29.5 years, most lived in urban areas (89%) with a mean travel time of 43.4 minutes required to get to the health center and 57.3 minutes to get the hospital. Ninety-six percent of women (n = 140) responded that they would like to receive text messages and cell phone calls with information regarding prenatal care, although the topics and period of time to receive information varied greatly. Conclusions Considering the vast majority of the interviewed women had access to and were interested in receiving text messages and calls with educational information regarding pregnancy and infant health, pregnant women in Argentina could benefit from such an mHealth program. The low access to Internet suggests it is not an option for this population; however, this cannot be assumed as representative of the country's situation. To retain active participation, other forms of health communication, such as a 2-way text message systems or toll-free numbers, could be considered in the future. Cost of use and implementing these options should be studied.